PENGARUH WEBSITE QUALITY, HEDONIC SHOPPING MOTIVATION¸ DAN PROMOSI PENJUALAN TERHADAP ONLINE IMPULSE BUYING PRODUK FASHION DI TOKOPEDIA - Satria, Satria; Yunita, Yunita (Journal Competency of Business, 2023)
This research aims to analyze the influence of website quality, hedonic shopping motivation, and sales promotions on online impulse buying of fashion products on Tokopedia. The data collection method uses a questionnaire distributed via Google Form. The population of this research are active students in Yogyakarta. Sampling was carried out using non-probability sampling with purposive sampling technique. The total sample was 108 respondents. The tests used in testing research instruments and questionnaire data include validity tests and reliability tests. The data analysis technique used is logistic regression analysis. The results of this research show that website quality, hedonic shopping motivation, and sales promotions have a positive and significant effect on online impulse buying of fashion products on Tokopedia